2017
DOI: 10.1021/acscatal.7b01061
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Nb–Pt Interactions To Facilitate Fuel Cell Electrocatalysis

Abstract: High stability, availability of multiple oxidation states, and accessibility within a wide electrochemical window are the prime features of Nb that make it a favorable candidate for electrocatalysis, especially when it is combined with Pt. However, Nb has been used as a support in the form of oxides in all previously reported Pt−Nb electrocatalysts, and no Pt−Nb alloying phase has been demonstrated hitherto. Herein, we report a multifunctional Pt−Nb composite (PtNb/NbO x -C) where Nb exists both as an alloying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 65 publications
(110 reference statements)
5
37
0
Order By: Relevance
“…Furthermore, it is noticed that the determined ECSA of the pristine Pt/C catalysts is smaller than their ECSA measured in acidic media 21 . The same observation has been made previously 35 , but…”
Section: Comparison Of Different Pt/c Catalysts For Adt Measurements supporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, it is noticed that the determined ECSA of the pristine Pt/C catalysts is smaller than their ECSA measured in acidic media 21 . The same observation has been made previously 35 , but…”
Section: Comparison Of Different Pt/c Catalysts For Adt Measurements supporting
confidence: 85%
“…The CVs display the typical features of Pt with hydrogen underpotential deposition (Hupd), double layer region, and Pt oxidation and reduction in the potential range of 0.15-1.10 VRHE. Also the CO stripping curves are similar to their counterparts recorded in conventional electrochemical cells 35 .…”
Section: Comparison Of Different Pt/c Catalysts For Adt Measurements supporting
confidence: 68%
“…Ghoshal et al [1] investigated metallic Nb and Nb oxide to support Pt. [8] They found strong ligand effect from metallic Nb to suppress the OH formation on Pt, thus enhancing the catalyst ORR activity. More recently, Ma et al [2] has reported a selective Pt head deposition on NbO x nails that was embedded in porous carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Alloying Pt with a non-noble metal is an effective strategy for lowering Pt loading, decreasing PEMFC costs, as well as improving ORR activity. Recently, Goshal et al [18], and Jia et al [19] demonstrated that platinum and niobium form an alloy with a high potential to enhance ORR activity. Pt interacts with Nb and NbO x , and Nb contributes to the suppression of Pt dissolution due to strong ligand effects, which enhance catalytic activity toward ORR [19].…”
Section: Introductionmentioning
confidence: 99%
“…Pt interacts with Nb and NbO x , and Nb contributes to the suppression of Pt dissolution due to strong ligand effects, which enhance catalytic activity toward ORR [19]. Pt-Nb/ NbO x loaded on carbon was tested as an electrocatalyst and demonstrated high activity and durability for both ORR and hydrogen oxidation reaction (HOR) [18]. This new electrocatalyst has significant potential for further improvement but more studies are required to better understand the Pt-Nb and Pt-NbO x interactions and tailor them to improve the catalyst's performance.…”
Section: Introductionmentioning
confidence: 99%